ANALISIS KRITERIA DAN PROSES SELEKSI KONTRAKTOR CHEMICAL SEKTOR HULU MIGAS: APLIKASI METODE DELPHI-AHP - Rifki Kurniawan; Sawarni Hasibuan; Rosalendro Eddy Nugroho (MIX: JURNAL ILMIAH MANAJEMEN, 2017)
Abstract. With an average production growth of 6-7 percent per year, the performanceof upstream oil and gas company PT Pertamina EP Asset 3 plays a strategic role forenergy security in Indonesia. Chemical material procurement activities is one of thecritical activities in the upstream oil and gas supply chain that supports the corporatestrategy of PT Pertamina because the magnitude of the risk if the chemical materialsupplied does not comply with the specification. The purpose of this study was toanalyze the criteria and the selection process of contractors key chemical material in thecontext of the sustainability of the supply chain of oil and gas PT Pertamina 3 using theDelphi method and Analytical Hierarchy Process (AHP). Consensus on the criteria ofchemical contractor PT Pertamina EP Asset 3 involves 8 experts obtained after goingthrough three rounds. The criteria weights in a row is the safety and the environment,price, quality, delivery, flexibility, and services. Safety and environmental issues in theupstream oil and gas industry is a strategic issue and a top priority in selectingcontractors chemical. Based on the analysis results generated priority contractor wasPT. Elnusa Petrofin, followed by PT. Eonchemicals Putra, PT. Sasfindo Multi Yasa,and PT. Top Birus spacious. PT Elnusa Petrofin superior in safety and delivery criteria,although still weak on service and price criteria.